Pretreatment of cotton spinning residues for optimal enzymatic hydrolysis: a case study using green solvents - Fockink, Douglas, H. (2020)
ABSTRACT: The effectiveness of imidazole and ionic liquid pretreatments for the conversion of cotton spinning residues (dirty cotton residue - DCR and cotton filter powder - CFP) into soluble sugars was investigated. DCR was pretreated with imidazole using temperatures and reaction times that were arranged in a 2(2) factorial design and pretreatment performance was evaluated by enzymatic hydrolysis. High glucan to glucose and xylan to xylose yields (78.0 and 94.9 mol %) were obtained from the solids produced at 140 degrees C and 2h (center point), which provided delignification levels of 45.5% (w.v(-1)). The same pretreatment condition was applied to CFP yielding only 16.0% (w.v(-1)) of delignification, but 75.8 mol % of glucan and 95.7 mol % of xylan were converted as their corresponding monomeric sugars after enzymatic hydrolysis. Both pretreated materials were subjected to a central composite design to find the best enzymatic hydrolysis conditions regarding substrate total solids (TS) and enzyme loading. More than 40 g.L-1 glucose was obtained from both pretreated materials at 13.7% w.w(-1) TS and 20 FPU.g(-1) glucan after 96 h of hydrolysis. Ionic liquid pretreatment of the same cotton spinning residues showed moderate delignification levels, accompanied by a change in biomass crystallinity from cellulose 1 beta to cellulose II. This turned to be very important to improve enzymatic hydrolysis yields. Therefore, biomass delignification and crystallinity confirmed to be key factors governing the enzymatic saccharification of cotton spinning residues.